2013
DOI: 10.1177/1545968313508472
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Light Therapy for Fatigue Following Traumatic Brain Injury

Abstract: Blue light therapy appears to be effective in alleviating fatigue and daytime sleepiness following TBI and may offer a noninvasive, safe, and nonpharmacological alternative to current treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 40 publications
(70 reference statements)
6
103
2
Order By: Relevance
“…It's also been suggested in other research [12]. TCLT found that increases the expression of growth factors in nerve cells, contributing to the regeneration of damaged brain tissue by the ECA.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…It's also been suggested in other research [12]. TCLT found that increases the expression of growth factors in nerve cells, contributing to the regeneration of damaged brain tissue by the ECA.…”
Section: Introductionmentioning
confidence: 60%
“…On the other hand, when specifically applied to the CNS, They have also had their related results to those found in animal models and in clinical use. Results have been found in research on neurological recovery in acute ischemic stroke [8], in psychiatric disorders [9], neuro-degenerative diseases [10], in healthy people [11] and TBI victims [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other forms of behavioral training/ adjustment of sleep habits (25) and blue light therapy (26) have shown preliminary encouraging results.…”
Section: Non-pharmacological Interventionmentioning
confidence: 99%